2010
DOI: 10.1007/s12350-009-9190-x
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of pre- and postsynaptic noradrenergic signaling in a rat model of adriamycin-induced cardiotoxicity

Abstract: Our results suggest that adriamycin-induced toxicity exhibits no change in presynaptic noradrenaline uptake, but decreased beta-adrenergic receptors in cardiac tissues, supporting a role for PET imaging of noradrenaline signaling in the study of anthracycline cardiotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 39 publications
4
18
0
Order By: Relevance
“…The cardiotoxicity is characterized by electrophysiological, biochemical and morphological alterations [4] leading to irreversible cardiac dysfunction [1] and to the development of overt heart failure [5]. Suggested contributors to DOX-induced cardiomyopathy include mitochondrial disruption [6], inadequate cellular energetic [7], formation of free radicals [89], apoptosis [10], inhibited expression of cardiomyocyte-specific genes [10], production of proinflammatory, reduction of antiinflammatory cytokines [11] and alteration of adrenergic system in the heart [1,12], but the patophysiology is still not completely understood [1, 610]. It is commonly accepted that DOX increases oxidative stress [9], which could be particularly harmful to cardiomyocytes with sparse antioxidant defense [13].…”
Section: Introductionmentioning
confidence: 99%
“…The cardiotoxicity is characterized by electrophysiological, biochemical and morphological alterations [4] leading to irreversible cardiac dysfunction [1] and to the development of overt heart failure [5]. Suggested contributors to DOX-induced cardiomyopathy include mitochondrial disruption [6], inadequate cellular energetic [7], formation of free radicals [89], apoptosis [10], inhibited expression of cardiomyocyte-specific genes [10], production of proinflammatory, reduction of antiinflammatory cytokines [11] and alteration of adrenergic system in the heart [1,12], but the patophysiology is still not completely understood [1, 610]. It is commonly accepted that DOX increases oxidative stress [9], which could be particularly harmful to cardiomyocytes with sparse antioxidant defense [13].…”
Section: Introductionmentioning
confidence: 99%
“…112,113 Although clinical data assessing the role of PET in early diagnosis, monitoring, and management in CTRCD is currently lacking, an experimental study in a rat model of adriamycin cardiotoxicity, utilizing PET imaging of noradrenaline signaling for assessment of anthracycline cardiotoxicity, demonstrated that after 3 weeks of adriamycin administration, there was a decrease in myocardial uptake of the beta-adrenergic antagonist, [3H] CGP12177. 114 However, it remains unclear whether beta receptor density, as assessed by PET, can serve as a marker for CTRCD in humans. 114 In a mouse model of anthracycline-induced cardiotoxicity, increased uptake of [(18)F]-CP18, a PET tracer for imaging apoptosis, was observed in the doxorubicin-treated group, thereby suggesting a potential role for detection of anthracycline-induced myocardial apoptosis.…”
Section: Positron Emission Tomography (Pet)mentioning
confidence: 99%
“…114 However, it remains unclear whether beta receptor density, as assessed by PET, can serve as a marker for CTRCD in humans. 114 In a mouse model of anthracycline-induced cardiotoxicity, increased uptake of [(18)F]-CP18, a PET tracer for imaging apoptosis, was observed in the doxorubicin-treated group, thereby suggesting a potential role for detection of anthracycline-induced myocardial apoptosis. 115 …”
Section: Positron Emission Tomography (Pet)mentioning
confidence: 99%
“…Table 2 provides an overview. Combinations of autonomic imaging agents have, for example, been used to identify an imbalance between presynaptic neuronal integrity and postsynaptic receptor density in progressive heart failure (18), to show that postsynaptic receptor density and downstream signaling may be impaired despite intact presynaptic catecholamine uptake in adriamycin-induced cardiotoxicity (19) or to show that parasympathetic muscarinic receptors may be upregulated after myocardial infarction (20).…”
Section: Beyond Nerve Terminal Functionmentioning
confidence: 99%